The Impact of Social Media Marketing on Brand Loyalty ("Journal "U". Economy. Management. Finance.", 2017)
Building and maintaining brand loyalty is an actual topic of many researches. Marketers use various tools to maintain customer loyalty to the brand. One such tool is the social media marketing (SMM). The article considers the content of social networks of Rostselmash (one of the world's largest producers of agricultural machinery) and the influence of SMM on brand loyalty.
Keywords: social media marketing; brand loyalty; content